The Political Economy of International Finance Corporation Lending - Axel Dreher; Katharina Richert (Center for Economic Studies and ifo Institute (CESifo), 2017)
The bulk of International Finance Corporation (IFC) lending benefits companies from rich countries, and projects in countries with middle income. Large conglomerates such as Lidl or Mövenpick have been among its direct beneficiaries. This contrasts to some extent with the IFC's official mandate, which is to finance poverty-reducing projects for which private capital is not available on reasonable terms. We investigate the drivers of this mismatch. According to our theory, the governments of industrialized countries where borrowing companies are based form coalitions with governments of middle-income countries where the projects are implemented. We therefore expect preferential treatment to be most pronounced when the representatives of both the recipient's and the company's countries are best able to collude in exerting their influence. We argue that this will be the case when both countries' governments are represented among the IFC's Board of Executive Directors, and when they have extraordinary clout with major IFC shareholders. Using data for more than 3000 IFC projects over the 1995-2015 period we show that the (joint) influence of these countries helps them to receive a disproportional share of IFC funding.
Keywords: F33; F53; F34; F35; 330; international finance; international bureaucracies; political economy